Estudio de caso de leptospirosis en machala en paciente de 13 años de edad - Chamaidan Ramón, Gisela Estefanía (2018)
Leptospirosis is a zoonotic disease caused by a bacterium called leptospira, which is transmitted through the urine of rats, cats or infected dogs, with roots being the most common source of human infection, clinical manifestations can be mild and Getting to see fatal is coming mainly in tropical regions. The domestic and peridomiciliary transmission of Leptospira is linked to activities of daily life and inadequate environmental conditions. It is estimated that there are more than 500,000 cases of leptospirosis annually worldwide, in Latin America the mortality rate is 10%. In Ecuador, the figures from 2014 to 2016 have been decreasing, in the province of El Oro, leptospirosis has decreased to 2014. Two phases of the disease are presented, the septicemic phase of febrile onset lasts between 4-7 days, the immune phase occurs in the second week of 4 to 30 days, circulating antibodies appear and serious symptoms occur. The most frequent clinical characteristics are: fever, headache, myalgia, jaundice, kidney damage, conjunctival infection and asthenia. In people who develop the disease can occur in different clinical forms: Anicteric leptospirosis is characterized by a nonspecific febrile syndrome, icteric leptospirosis or Weil syndrome systemic involvement is presented as kidney failure, meningitis, pneumonia, hemorrhagic manifestations. In diagnostic tests the most used serological technique is the MAT macroscopic agglutination test, it determines the ability of the serum to bind specific Leptospira, in this way the presence of the bacteria is confirmed, specific IgM and IgG titers determine the corresponding serovar, arrives to determine the diagnosis by means of ELISA and the rest of laboratory exams. The treatment will depend on the severity of the disease. In cases of mild leptospirosis, oral drugs such as doxycycline or ampicillin can be used, and in moderate or severe cases, crystalline penicillin G or third-generation cephalosporins, such as ceftriaxone, are used. A review of the clinical history of a diagnosis of leptospirosis was made, through this case study of a male patient, aged 13 years, in the month of June 2017, at the Teófilo Dávila General Hospital. The type of study that was used was descriptive because it listed the clinical manifestations that occurred in a child with leptospirosis, performing a thorough and accurate analysis of our study unit, the method used was the clinician because the case was analyzed of a patient, heuristic because questions are born to obtain answers and analytical because the categories of the unit of analysis are broken down. The techniques and instrument that was performed were the documentary review of the clinical history to analyze the most important data of the unit of analysis such as the patient, the bibliography review to know the theoretical part of the characteristics of leptospirosis and the analysis categorization. from personal, family, vital signs, current status, diagnosis, physical examination, laboratory, radiological, treatment and nursing actions.